The Completion Effect in Charitable Crowdfunding - Klinowski-Gomez, D (Elsevier B.V., 2020)
We analyze data from two charitable crowdfunding platforms and find that donors make significantly larger donations, more frequently, and at a faster pace, in order to personally reach fundraising targets. This ‘completion effect’ occurs even when the target is of no consequence for provision, and even within donors who make multiple contributions on a platform. While the majority of donors follow suggested gift amounts at other points of the campaign, they deviate upwards in order to personally reach targets. We provide evidence that the effect is not driven by uncertainty about the recipient s ability to reach the fundraising goal; rather, it appears to be driven by a private benefit to the donor from personally completing campaigns. © 2020 Elsevier B.V.